A Control Circuit Design for Automatic Aperture. (September 2020) - Cao, Yong; Zheng, Yifan; Liu, Yi; Wang, Xiao; Hu, Jinrui
Abstract: In view of the fact that automatic aperture technique is applied as a method of regulating light in the current industrial monitoring and control systems more and more, an automatic aperture control circuit is designed according to automatic aperture control principle. The circuit has the characteristics of the simple structure, low cost and high reliability and etc. It has been proved by experiments that the circuit can adjust the size of aperture automatically according to the change of the external illumination, which ensures proper luminous flux entering the lens, and avoids the loss of image gray levels in bright space, and solves the image flicker caused by the change of light intensity, ensures the CCD get used to brightness changes of scenery outside and obtain the best image.